Lithuanian copy-editors in the fields of language standardization and cultural production: negotiating competing notions - Jankauskaitė, Eglė (Taikomoji kalbotyra, 2022)
Copy-editors are important agents of language standardisation, yet Following Pierre Bourdieu’s field theory, as well as Michel Foucault’s power/knowledge dichotomy, in this article I am analysing data from semi-structured interviews with 21 Lithuanian copy-editors to determine how they negotiate their often-opposing professional notions on editing ethics and practice. The analysis has shown that in terms of ethical notions, copy-editors maintain that editing “too much” is unethical. This is likely based on the rules of the game of the literary field. It has been noticed, that the editors who also have other roles in the literary field, more strongly oppose the practice they called “author production”. Some copy-editors, however, who did not have such high stakes in the literary field, seemed to sometimes take on this work of “too much” editing, but in an interview situation, they claimed that such practice is different from copy-editing.